Eye of the beholder : Johannes Vermeer, Antoni van Leeuwenhoek, and the reinvention of seeing /: Johannes Vermeer, Antoni van Leeuwenhoek, and the reinvention of seeing. (2015) - Snyder, Laura J
No abstract available